Brunei Darussalam : 2019 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation highlights that Brunei's economy has been adjusting to declining oil production since 2010 and lower oil and gas (O and G) prices since 2014, with the authorities undertaking wide-ranging reforms. Growth is expected to pick up in 2019 to 1.8 percent, with the outlook improving further over the medium term, driven by stronger O and G activities from asset rejuvenation and large foreign direct investment projects. The authorities have made substantial progress in fiscal consolidation, improving the business climate, and developing the financial sector. The fiscal consolidation initiatives include corporatization and privatization, public-private partnership, evaluation of subsidies against targets, fiscal management enhancement, revenue diversification, and amalgamation of the government's asset management system. The IMF staff supports the authorities' initiatives to develop the financial sector, while safeguarding financial stability and integrity. The initiatives include steps to broaden the investor base, establish a secondary bond market, develop the required infrastructure and rules for establishing a stock exchange, and put all the three pillars of Basel II in place.